Galanin-3 Receptor Antagonism by SNAP 37889 Reduces Motivation to Self-administer Alcohol and Attenuates Cue-Induced Reinstatement of Alcohol-Seeking in iP Rats - Belinda L. Ash; Tim Quach; Spencer J. Williams; Andrew J. Lawrence; Elvan Djouma (Elsevier, 2014)
Abstract.: The neuropeptide galanin has a role in promoting alcohol consumption and general feeding behavior. The galanin-3 receptor (GALR3) subtype is implicated in modulating the consumption of alcohol and has therefore been identified as a potential target for new pharmacotherapies to treat alcohol use disorders. We have previously shown that the selective GALR3 antagonist SNAP 37889 reduced voluntary alcohol consumption in iP (alcohol-preferring) rats. The present study firstly aimed to investigate the effect of GALR3 antagonism on the motivational properties of alcohol. Secondly, the potential of GALR3 as a therapeutic target in the prevention of relapse was investigated in response to alcohol-conditioned cues. Administration of SNAP 37889 (30 mg/kg, i.p.) significantly reduced the breakpoint for ethanol under a progressive-ratio operant responding schedule of reinforcement. SNAP 37889 also significantly reduced reinstatement of alcohol-seeking in response to re-exposure to conditioned cues that were previously associated with the availability of alcohol. Collectively, results from the current study provide new evidence of GALR3 involvement in cue-induced relapse and provide further evidence that GALR3 antagonism reduces the motivational drive to consume alcohol. These findings validate further research in to the potential use of SNAP 37889 and other GALR3 antagonists to treat alcohol abuse disorders in humans. Keywords:: alcohol, galanin, galanin-3 receptor (GALR3), operant self-administration, cue-induced reinstatement